Formulation And Evaluation Of Nanoemulgel Clove Leaf Oil (Sygyzium Aromaticum) (L.) Merr & Perry As Anti-Acne - Dasawanti, Yoan; Reveny, Julia; Sumaiyah, Sumaiyah (Publisher Cv. Inara, 2022)
Acne also known as acne vulgaris, is an inflammatory condition of the polysebaceous layer that is brought on by the buildup of keratin. Active oil glands under the skin cause acne. Androgen hormones function as a stimulant for this activity. Cloves are herbal plants that contain essential oil chemicals. The chemical composition of clove leaf oil is mainly composed of eugenol. Eugenol has pharmacological effects as antibacterial, analgesic and anti-inflammatory. Nanoemulsion is a nanocarrier that gets a lot of attention, because of its small particle size so that it can be thermodynamically stable and can increase drug penetration. Recent advances in nanoemulsion research have created new prospects in a number of industries, including pharmaceuticals, biotechnology, food, and cosmetics. This research was conducted by formulating clove leaf oil into nanoemulgel preparations, followed by evaluation of the preparations and testing of antibacterial activity against acne-causing bacteria. The result of the nanoemulgel formulation is yellow, smells of clove leaf oil, is transparent and homogeneous. Nanoemulgel viscosity 3434-3109 M.Pas, pH 6.15-6.41 and particle size 12.3-13.3 nm. Physical studies of nanoemulgel been carried out for three cycles and there is no change in color, change in odor and phase separation. The results of the antibacterial activity of Staphylococcus epidermidis at NEG1 12.03 mm, NEG2 16.93 mm, NEG3 18.96 mm and EG 18.03 mm. The results of the antibacterial activity of Propionibacterium acnes at NEG1 11.50 mm, NEG2 16.16 mm, NEG3 18.03 mm and EG 17.33 mm. The results of the study concluded that clove leaf oil nanoemulgel with a concentration of 7% was the best formula, because it is stable during storage and has the greatest antibacterial activity compared to emulgel.